2013
DOI: 10.1021/mz400464d
|View full text |Cite
|
Sign up to set email alerts
|

Iridescent Chiral Nematic Cellulose Nanocrystal/Polymer Composites Assembled in Organic Solvents

Abstract: We describe an approach to prepare polymer composites with chiral nematic photonic structures through the self-assembly of cellulose nanocrystal (CNC) dispersions in organic solvents. Contrary to previous reports, we demonstrate that dispersions of neutralized sulfated CNCs in polar organic media readily form lyotropic chiral nematic liquid crystalline phases. We have investigated the effect of the neutralizing base on the CNC self-assembly, observing chiral nematic ordering for all counterions studied. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 44 publications
1
98
0
4
Order By: Relevance
“…34 In fact, iridescent germaniumcontaining composites with chiral nematic ordering can be obtained easily, but the pyrolyzed samples were fragile and we were unable to remove the CNC template by calcination without substantial loss of chirality and structure in the films. 34 In fact, iridescent germaniumcontaining composites with chiral nematic ordering can be obtained easily, but the pyrolyzed samples were fragile and we were unable to remove the CNC template by calcination without substantial loss of chirality and structure in the films.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…34 In fact, iridescent germaniumcontaining composites with chiral nematic ordering can be obtained easily, but the pyrolyzed samples were fragile and we were unable to remove the CNC template by calcination without substantial loss of chirality and structure in the films. 34 In fact, iridescent germaniumcontaining composites with chiral nematic ordering can be obtained easily, but the pyrolyzed samples were fragile and we were unable to remove the CNC template by calcination without substantial loss of chirality and structure in the films.…”
Section: Resultsmentioning
confidence: 99%
“…These materials have pores about 3-10 nm in diameter that are organized into a layered, helicoidal arrangement. 33 Recently our group 34 and Gray et al 35 demonstrated that lyotropic chiral nematic LC phases can be formed by dispersing neutralized sulfated CNCs in polar organic media such as N,N-dimethylformamide (DMF). It is worth noting that the chiroptical properties of these photonic materials can be tuned by simply changing the length of the helical pitch.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 These attractive properties have motivated numerous endeavors toward fabricating multifunctional CNC nanocomposites using solution casting, melt processing, sol–gel, and template methods, 1,5,7 which may yield the typical low filling fraction nanocomposites (<40 mass %) or highly filled biomimetic composites with cholesteric self-assembled CNCs. 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…The CNC/polymer hydrogels obtained showed changes in iridescence in response to external stimuli such as solvent, pH, or temperature. Iridescent CNC/polymer composites were also produced solely by slow evaporation of chiral nematic dispersions of CNC (~3.5 wt%) in DMF, which were mixed in advance with a commodity polymer such as polystyrene or poly(methyl methacrylate) [126]. To obtain the stable liquid crystalline suspensions of CNCs in such a polar organic solvent, sulfuric acid-hydrolyzed CNCs were neutralized with a strong base (LiOH, NaOH, KOH, etc.)…”
Section: Polymer Composites With Liquid Crystalline Cncsmentioning
confidence: 99%